Capturing the whole-school food environment in primary schools - Sarah E Moore; Sarah F Brennan; Fiona Lavelle; Moira Dean; Michelle C McKinley; Dilara Olgacher; Patrick McCole; Ruth F Hunter; Laura Dunne; Niamh E O'Connell; Chris T Elliott; Danielle McCarthy; et al. (Cambridge University Press, 2023)
Abstract Objective: The school food environment (SFE) is an ideal setting for encouraging healthy dietary behaviour. We aimed to develop an instrument to assess whole-SFE, test the instrument in the school setting and demonstrate its use to make food environment recommendations. Design: SFE literature and UK school food guidance were searched to inform instrument items. The instrument consisted of (i) an observation proforma capturing canteen areas systems, food presentation and monitoring of food intake and (ii) a questionnaire assessing food policies, provision and activities. The instrument was tested in schools and used to develop SFE recommendations. Descriptive analyses enabled narrative discussion. Setting: Primary schools. Participants: An observation was undertaken at schools in urban and rural geographical regions of Northern Ireland of varying socio-economic status (n 18). School senior management completed the questionnaire with input from school caterers (n 16). Results: The instrument captured desired detail and potential instrument modifications were identified. SFE varied. Differences existed between food policies and how policies were implemented and monitored. At many schools, there was scope to enhance physical eating environments (n 12, 67 %) and food presentation (n 15, 83 %); emphasise healthy eating through food activities (n 7, 78 %) and increase parental engagement in school food (n 9, 56 %). Conclusions: The developed instrument can measure whole-SFE in primary schools and also enabled identification of recommendations to enhance SFE. Further assessment and adaptation of the instrument are required to enable future use as a research tool or for self-assessment use by schools.